2020
DOI: 10.1016/j.surg.2020.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Patient complexity by surgical specialty does not correlate with work relative value units

Abstract: Background: Understanding the differences in how patient complexity varies across surgical specialties can inform policy decisions about appropriate resource allocation and reimbursement. This study evaluated variation in patient complexity across surgical specialties and the correlation between complexity and work relative value units. Study design: The 2017 American College of Surgeons National Surgical Quality Improvement Program was queried for cases involving otolaryngology and general, neurologic, vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…The result of a study done in Korea illustrated that there is still a debate between different medical specialties over the unfair value structure (21). Sadeghi et.al concluded that the professionals in the health system is not completely satisfied with the RVU's book, they thought the new book has failed to establish interdisciplinary justice (9) It is expected that the health systems will face a shortage of specialist staff in some critical specialties in the next few years (23).Sigsbee shows that physician's income gap in the United States made it hard to attracting volunteer physician for some medical specialties, therefore, it is necessary to pay attention to RVU as the basis for physician reimbursement system (24) Of course, injustice is inherent in the structure of RVU. Although this study focused on the challenges of relative value in Iran, it is necessary to note some of the RVU's challenges are inherent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The result of a study done in Korea illustrated that there is still a debate between different medical specialties over the unfair value structure (21). Sadeghi et.al concluded that the professionals in the health system is not completely satisfied with the RVU's book, they thought the new book has failed to establish interdisciplinary justice (9) It is expected that the health systems will face a shortage of specialist staff in some critical specialties in the next few years (23).Sigsbee shows that physician's income gap in the United States made it hard to attracting volunteer physician for some medical specialties, therefore, it is necessary to pay attention to RVU as the basis for physician reimbursement system (24) Of course, injustice is inherent in the structure of RVU. Although this study focused on the challenges of relative value in Iran, it is necessary to note some of the RVU's challenges are inherent.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the existing RVU method can include inaccuracies due to the surgeon's work calculation (25) According to experts, the RVUs do not differentiate between acute and elective surgeries, while it is obvious, acute surgeries require time and surgeon's effort more. Unfairly reimbursement for acute care surgery can discourage trainees from pursuing as acute care surgeons or accepting emergency general surgery calls, possibly leading to a shortage of acute care surgeons (23,26). The evidence shows that physicians' dissatisfaction can result in induced demand and illegal payments (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that it is difficult to quantity the complexity of the patient serviced by physicians in outpatient clinics in the diagnosis and treatment also with no accepted measures, patient difficulty served by a physician in the diagnosis and treatment could be simply measured based on the question that “did you have any patients that you perceived as difficult?” reported in previous research ( 23 ) and another study reported some domains such as number of major comorbidities, major complications, and operation could be used as a measure of patient complexity by surgical specialty ( 40 ). And accordingly, we used the ratio of the number of outpatients serviced per day admitted to the hospital by a physician for further diagnosis or treatment to the number of outpatients seen per day by the physician as the measure of served patient complexity in this study; and to avoid that the ratio was zero, we normalized this ratio and added 1, that is, 1 represents the reference value.…”
Section: Methodsmentioning
confidence: 98%
“…Surgical patient complexity has no agreed upon definition, but generally increases with the number of patient comorbidities and medications, the need for an emergent operation or additional procedures and an American Society of Anesthesiologists physical classification of IV or greater. [17][18][19] A patient with a "high acuity" generally implies a severe physiologic status in terms of vital signs or laboratory data, a high mortality risk, intense resource needs including nursing care, medications, or blood products and includes high patient complexity. 20 In trauma or critical illness, a high-acuity patient is resource intensive and requires multiple lifesaving interventions in a short period.…”
Section: Readinessmentioning
confidence: 99%